Brachial plexitis complicating disseminated gonococcal infection. Issue 760 (February 1989) - Maroun, B.; Rimon, D.; Cohen, L.
Abstract : A patient with brachial plexitis associated with disseminated gonococcal infection is presented. This is, to the best of our knowledge, the first case to be reported of this association.